A laboratory investigation on the shear strength characteristics of soil reinforced with recycled linear low-density polyethylene - Nolutshungu, Lita (Geotechnical Engineering Research Group, 2019)
Since the development of plastics in the 1930’s, plastics have increasingly become widely used for packaging in the commercial market place. With this application being for immediate disposal, the amount of plastic waste generated presents a challenge in the disposal thereof. The risks associated with non-biodegradable products on humans and animal life, pressure on existing landfills and the increasing costs thereof have necessitated the development of alternative options for waste management over the years. Research has resulted in various forms of treatments and recycling processes adopted and implemented as environmentally and economically viable solutions. The use of this recycled material in various applications, such as soil reinforcement addresses the need for engineering solutions with a multifaceted approach which strike a balance between environment, economy and equity. This has been the driving force behind research on the use of alternative materials in engineering design. This study aimed to present an investigation into the use of recycled Linear Low-Density (LLDPE) as reinforcement in Cape Flats sand. To understand the implication of the main aim of the investigation, a review of literature on soil reinforcement theory, various forms of reinforcement material and previous studies was conducted. The selected material for testing was in the form of pellets and flakes produced during the recycling process. Triaxial tests were done on samples where the concentration of the inclusions and compaction effort was varied. The test data presented showed that both pellets and flakes affected the shear strength by plotting Mohr’s circles and the relationship between shear stress and normal stress, which revealed changes in the shear strength parameters. The friction angle was increased by 3.35% at an optimum pellet concentration of 5%. Inclusion of the flakes, however, resulted in a maximum improvement in cohesion of 295% at 0.25% concentration. A discussion on the stress- strain relationship gave an indication on the effect on the stiffness. This showed that the peak shear stress was reached at higher strains when the flakes and pellets were included, compared to the unreinforced sand. Improvements by up to 25% were recorded from the initial 6% strain at peak shear stress of unreinforced sand. In concluding the study, Slide7.0 was used to conduct a 2D finite element analysis using Bishop’s method to analyse the practical application of LLDPE flakes and pellets for slope stability. The optimum shear strength parameters were used in the model, which resulted in an improved global factor of safety meeting the minimum requirement of 1.25.